Implementación de un sistema de señalética en el tema de seguridad industrial para el laboratorio del Taller Mecánico. - Iñiguez Guachizaca, Joffre Favian (2012)
This research work has as its primary objective the implementation of the appropriate signage for the laboratory machine shop knowing that every shop should have the respective signals so that it becomes a safer place for this reason that it is disturbing the "IMPLEMENTATION OF A SYSTEM OF SIGNAGE ON THE SUBJECT OF INDUSTRIAL SAFETY LABORATORY MECHANICAL WORKSHOP". Keep in mind always that good industrial safety can prevent countless accidents and therefore is a way to safeguard the human life. Although adequate signage alone does not eliminate the risk, if it helps to avoid mistakes due to ignorance of risk, and that is where the research theme comes into play an important role to minimize or mitigate the severity and / or frequency of accidents, to make evident the risk and precautions that the person should take in implementing its work.